Penggunaan Hipnoterapi Untuk Mengatasi Insomnia Pada Lansia - Noyumala Noyumala; Jukarnain Jukarnain; Muslimin B; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Insomnia is a sleep disorder frequently experienced by the elderly and impacts quality of life, physical health, and psychological well-being. Treatment of insomnia in the elderly is often hampered by the side effects of long-term use of sleeping pills. Hypnotherapy is a non-pharmacological therapy that can be used to safely and effectively address sleep disorders. This Community Service activity aims to improve the sleep quality of the elderly through the application of simple hypnotherapy. Implementation methods include education about insomnia in the elderly, training in basic hypnotherapy techniques, guided relaxation practice, and evaluation through pre- and post-tests. The results of the activity showed a decrease in insomnia complaints and an improvement in sleep quality in the elderly after participating in hypnotherapy sessions. Hypnotherapy can be an effective and safe alternative complementary therapy for treating insomnia in the elderly.